Inclusive Education and Papuan Literature for Diversity and Equality - Adi Iwan Hermawan; Maman Suryaman; Kastam Syamsi; Ismail Marzuki; Ho Ngoc Hieu (LP. Ma'arif Janggan Magetan, 2025)
This study, titled Inclusive Education and Papuan Literature for Diversity and Equality, aims to develop inclusive education teaching materials grounded in Papuan literary culture to foster values of equality and diversity in the educational context of Eastern Indonesia. Using a research and development (R&D) approach, the study adopts Plomp’s model, consisting of five systematic phases: initial investigation, design, realization, test-evaluation-revision, and implementation. The research was conducted at SMP Negeri 1 Sorong Regency, involving 21 Grade VII students. Data were gathered through expert validation—covering content, media, and language aspects—and teacher feedback on the practicality of the materials. The effectiveness test revealed an improvement in student learning outcomes, with a gain score of 0.46, categorized as moderate (0.3–0.7 range). Theoretically, this study contributes to the integration of local cultural narratives into inclusive literacy instruction, strengthening frameworks of multicultural and place-based learning. Its novelty lies in leveraging the literary richness of Papua to develop adaptive, inclusive literacy materials. Practically, the resulting product serves as a validated, practical, and effective model applicable in 3T (frontier, outermost, and disadvantaged) regions, promoting students' cultural identity, tolerance, and active engagement in learning.